Hispanic/Latino Concerns about Living Kidney Donation: A Focus Group Study. (June 2014) - Gordon, Elisa J.; Mullee, Jack O.; Ramirez, Daney I.; MacLean, Jessica; Olivero, Maria; Feinglass, Joseph; Carney, Paula; O'Connor, Kate; Caicedo, Juan Carlos
Context: Given the shortage of kidneys for transplant, living kidney donation (LKD) is increasingly used to expand the organ donor pool. Although Hispanics/Latinos need disproportionately more kidney transplants, they receive a smaller proportion of living donor kidney transplants than other ethnic/racial groups. Objective: To assess Hispanics' awareness, perceptions, misconceptions, cultural beliefs, and values about and barriers to LKD. Design: Nine focus groups were conducted with 76 adult Hispanics in Chicago, Illinois, between January and March 2012. Participants: Focus groups included kidney transplant recipients, living kidney donors, dialysis patients, and the general Hispanic public. Results: Several themes emerged as perceived barriers to LKD. Many participants identified knowledge deficits about LKD, expressing uncertainty about the differences between LKD and deceased donation, and whether kidney disease simultaneously afflicts both kidneys. Many believed that donors experience dramatically shorter life expectancies, are unable to have children, and are more susceptible to kidney disease after donating. Recipients and donors reported that family members were involved in discussions about the donor's decision to donate, with some family members discouraging donation. Financial barriers cited included fear of becoming unable to work, losing one's job, or being unable to pay household bills while recovering. Participants also identified logistic barriers for undocumented immigrants (eg, the inability to obtain government insurance for transplant candidates and uncertainty about their eligibility to donate). Donors desired information about optimizing self-care to promote their remaining kidney's health. Culturally competent interventions are needed to redress Hispanics' knowledge deficits and misconceptions and reduce LKD disparities among Hispanics.